ANALISIS PENYESUAIAN DIRI SISWA REMAJA AWAL YANG BERSEKOLAH DI KOTA DAN DI DESA - Cahyaning Asnikaweny; Elni Yakub; Zulfan Saam (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract : Self- adjusment of students who attend school in the city while there are still less able to controlling emotion and less respect for others so that they can’t adjust to existing regulations. While the attainment of self-adjusment in the village has been able to respect others with people of help and not to think about the difference in socialize. According to this case, researcher feels necessary to analyze the adjustment of early adolescences who attend school in the city and village. The purpose of this study are to find out the adjustment of students who attend school in the city and in the village and to find out the self-adjusment seen from the aspects of adjustment. This research uses descriptive qualitative method. Data collection techniques use questionnaires. Data analysis uses techniques percentages. Populations and sample in this study were 212 students. The results of this study are: Adjustment of students in the city and villages are both in the medium category, although the percentage of adjustment in the city is higher than in the village. Aspect that are in the good category of aspect in the consideration ang direction of the rasional and aspect in using the experience of the past, both in the city and in the village. But the differences are not seen significantly, but in this developed era both school in the city and village have not difference in the adjustment.Key word : Self-Adjustment, Adolescence, City and Village